Investor education and trading activity on the stock market. Issue 2 (2nd July 2016) - Liivamägi, Kristjan
ABSTRACT: This study analyses how investors' educational characteristics affect their trading activity on the stock market. It uses a unique dataset from the Tallinn Stock Exchange, covering all transactions of a full business cycle from 2004 to 2012, along with a dataset containing the official educational background for all individual investors. Applying an ordered logit regression model and controlling for gender, age, wealth, portfolio diversification and average stock holding period, this study provides empirical evidence that the investors with top results in national exams or the investors holding an academic degree trade stocks more actively. The opposite is true for the investors with no academic degree as they trade stocks less actively. Analysing investors' risk-adjusted performance reveals that trading experience in the form of trading activity is the contributing factor for higher returns on the stock market.